2003
DOI: 10.1159/000074566
|View full text |Cite
|
Sign up to set email alerts
|

PCR with the Aqueous Humor, Blood Leukocytes and Vitreous of Patients Affected by Cytomegalovirus Retinitis and Immune Recovery Uveitis

Abstract: Purpose: To detect the cytomegalovirus (CMV) genome by PCR in the aqueous humor, blood leukocytes and vitreous of patients affected by retinitis and immune recovery uveitis (IRU). Methods: A PCR for CMV genome detection was carried out with the aqueous humor, vitreous and blood leukocytes of 54 patients with retinitis, including 25 HIV-infected patients presenting CMV retinitis in different stages (active lesion 6 cases, healed lesion 14 cases and IRU 5 cases), and 29 non-HIV-infected patients (retinitis unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…A recent study on HIV-positive patients with IRU showed the absence of CMV genome on the PCR analysis, supporting the hypothesis that IRU is not directly related to viral replication in the eye (6).…”
Section: Discussionsupporting
confidence: 54%
“…A recent study on HIV-positive patients with IRU showed the absence of CMV genome on the PCR analysis, supporting the hypothesis that IRU is not directly related to viral replication in the eye (6).…”
Section: Discussionsupporting
confidence: 54%
“…We are indebted to Klaus Roemer for critical review of the manuscript. GAA ACG CGC G C GC AAT CGG 81873-81890 2, 3, 9, 12, 22 R2 (9,12,22) TAC GCT GCA GTT CAC/CCC AG 82055-82036 2 R3 (11) T-G AAC TGG AAC GTT TGG C 82174-82156 2, 8, 9, 12, 13, 22 F4 (18, 19) CGG AAA CGA TGG TGT AGT TGG 82571-82591 R5 (18,19) TCC AAC ACC CAC T/AG ACC GGT 82838-82818 F6 (15) ATA GGA GGC GCC ACG TAT TC …”
mentioning
confidence: 99%